IMPLEMENTASI PENDIDIKAN BUDAYA DAN KARAKTER BANGSA DALAM BUDAYA SEKOLAH - Susanto, Rochmad Dwi; Zuriah, Nurul; Syahri, Mohamad (Civic Education Department, Faculty of Teacher Training and Education, University of Muham, 2017)
Education and culture to be very fundamental national character is created and maintained for the values of good character , namely : value , religious , honest , tolerance , discipline , hard work , creative, independent , democratic , curiosity , the spirit of nationalism , patriotism , appreciate the achievements , friends / communicative , love peace , love reading , environmental care , social care and responsibility . This research was conducted at SMP Negeri 3 Malang , with the aim of : ( 1 ) To describe the implementation of National Character Education Culture And Culture In Schools